(untitled) (IAHS Medical Journal, 2024)
Background: The proportion of hospitalizations attributable to infectious diseases is high, and likely to increase further in the future as a result of the expected aging of the population and the increasing prevalence of comorbid conditions among the elderly. The present study aimed to investigate the clinical characteristics and outcomes of elderly patients admitted due to infection in a tertiary-level hospital in Chattogram, Bangladesh. Materials and methods: This prospective observational study was conducted in Chittagong Medical College Hospital (CMCH) Chattogram. Two hundred and six patients aged ≥60 admitted with a diagnosis of infectious aetiology in the medicine department were enrolled according to set inclusion criteria. Patients were followed up for in-hospital outcomes after admission. Results: Age ranges from 60-90 years with a mean age of 65.82 (±5.56) years) and 51.5% were male. Pre-hospital antibiotic was received by 108 (52.4%) patients and 7.4% had antibiotic prescribed by registered physicians The most frequent infections were respiratory tract infections (47.6%) and urinary tract infections (43.2%). Sixty-four (31.1%) patients developed sepsis and 17 (8.3%) required ICU support. Eleven patients expired in-hospital, indicating a mortality rate of 5.3%. Length of hospitalization ranged from 2 to 17 days, with a median of 6 days. Conclusion: This study result suggests that infection-related hospitalization and outcomes of elderly individuals were high and their health seeking behaviour was poor. IAHS Medical Journal Vol 6(2), December 2023; 31-34